2013
DOI: 10.1155/2013/351936
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Study Comparing Helical Blade with Screw Design for Sliding Hip Fixations of Unstable Intertrochanteric Fractures

Abstract: Dynamic hip screw (DHS) is a well-established conventional implant for treating intertrochanteric fracture. However, revision surgery sometimes still occurs due to the cutting out of implants. A helical blade instead of threaded screw (DHS blade) was designed to improve the fixation power of the osteoporotic intertrochanteric fracture. In this study, the biomechanical properties of DHS blade compared to the conventional DHS were evaluated using an unstable AO/OTA 31-A2 intertrochanteric fracture model. Fifty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…13,17,18 But we believe that this situation doesn't simulate the real stance. Because load to failure under such a condition eventually leads a failure from femoral head.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…13,17,18 But we believe that this situation doesn't simulate the real stance. Because load to failure under such a condition eventually leads a failure from femoral head.…”
Section: Resultsmentioning
confidence: 93%
“…Theoretically it offers the potential of resisting rotation and a better holding power in osteoporotic femoral head with compaction of cancellous bone and can decrease the rate of cutting out. 13,14 As a matter of fact, several clinical and experimental studies were published after ıntroduction of the single helical blade. Although studies comparing two lag screws with a single helical blade concluded the biomechanical and clinical superiority of single helical blade.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the DHS blade shows a higher rotational stability and resistance to push out compared to the conventional screw [16,17], we decided to use the helical blade to achieve the most stable conditions for the extramedullary osteosynthesis. Furthermore, an additional, angular stable, trochanteric stabilization plate was implanted to ensure maximum stability.…”
Section: Methodsmentioning
confidence: 99%